Picturing perspectives: development of perspective-taking abilities in 4- to 8-year-olds - Frick, Andrea; Möhring, Wenke; Newcombe, Nora S. (Frontiers in Psychology, 2014)
Although the development of perspective taking has been well researched, there is no uniform methodology for assessing this ability across a wide age span when frames of reference conflict. To address this gap, we created scenes of toy photographers taking pictures of layouts of objects from different angles, and presented them to 4- to 8-year-olds (N = 80). Children were asked to choose which one of four pictures could have been taken from a specific viewpoint. Results showed that this new technique confirmed the classic pattern of developmental progress on this kind of spatial skill: (1) 4-year-olds responded near chance level, regardless of layout complexity, (2) there was a growing ability to inhibit egocentric choices around age 6 with layouts of low complexity (one object), (3) performance increased and egocentric responses decreased dramatically around age 7, (4) even at age 8, children still showed considerable individual variability. This perspective taking task can thus be used to address important questions about the supports for early spatial development and the structure of early intellect.